Molecular characterization and cultivar identification in Bougainvillea spp. using SSR markers - KUMAR, P PAVAN; JANAKIRAM, T; BHAT, K V; JAIN, RITU; PRASAD, K V; PRABHU, K V (The Indian Journal of Agricultural Sciences, 2014)
The present study was undertaken to determine the genetic relatedness and molecular characterization of fifty bougainvillea cultivars that belong to four major species of bougainvillea namely B. glabra, B. spectabilis, B.peruviana and Bougainvillea × buttiana. Five microsatellite (simple sequence repeat; SSR) markers with high PIC values were used to characterize these bougainvillea cultivars. A total of 28 alleles were detected at an average number of alleles of 5.6 alleles /locus. The PIC values varied widely among primers and ranged from 0.364 to 0.891 with an average of 0.716 per locus and the size of the amplified products ranged from 90bp to 250bp. Primer BOUG-1 showed the highest polymorphism index content (0.891) thus reflecting it’s ability to differentiate these cultivars much better at molecular level. A total of 18 rare alleles were identified among which the cultivar (Blondie) had maximum number of rare alleles (3). An unweighted pair group method cluster analysis (UPGMA) based on similarity values revealed five main clusters with Cluster I being the largest one encompassing 18 cultivars while cluster IV and V emerged as the smallest ones comprising 3 cultivars each. The pair wise estimates of genetic distance ranged from 0 (Cherry Blossom to Mary Palmer Special) to 1.0 (Blondie to Shubhra, Partha, Lady Hope, Gloriosus, Red September, Zakiriana, Lady Richards and Spledens). The present investigation is first of its kind in using microsatellite markers for phylogenetic analysis and molecular characterization in bougainvillea cultivars. The study proved the efficiency of SSR markers in documentation, identification and tracing out the molecular origin among unknown cultivars of bougainvillea.